The technology takers : leading change in the digital era - Flanding, Jens P.; Grabman, Genevieve M.; Cox, Sheila Q. (Emerald Publishing Limited, 2018)
Users of twenty-first century, digital-era technologies are "technology takers," accepting of and adjusting to whatever the market offers them. Similar to small firms that lack the market power to set prices and are economic "price takers," managers today are increasingly unable to customize the digital-era technologies their organizations use. Technology takers have little influence over the capabilities of the technologies they adopt; they cannot expect to improve on or customize for themselves the features of Facebook, Google, the iPhone, the blockchain, cloud-based enterprise resource planning systems, or other game-changing and often disintermediating technologies.The inability to modify available information technologies is a shock to leaders and managers alike. Cloud-based technologies arrive with set processes developed by others, and users must learn new ways of working each time the technologies themselves evolve. But refusing to adopt and adapt to digital-era technologies is, increasingly, not an option. Change in the digital era is constant and behavior-transforming. Managers must respond to these changes, or they will get left behind by those who do. The constancy of change also means that organizations have to do more than launch typical, one-off change management or transformation projects to succeed.To adopt efficiently and adapt effectively to behavior-changing technologies, astute leaders should employ change leadership techniques as a strategy for the digital era. This book offers technology takers a playbook to manage change, create value, and exploit the digital era's strategic opportunities. The book draws on research and recent case studies to explain what it means to be a technology taker. Organizations and their managers are offered change leadership plays, which emphasize the iterative nature of change management in the digital era. The book also describes how technology taking can create value through data stream analytics and be used strategically to respond proactively to the challenges of the digital era.